Penyuluhan Tentang Pengaruh Gadget Terhadap Anak Usia Dini Di SDN 1 Sopet Jangkar Situbondo - Elfa Yuliana; Hilwa Wafin Nur (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2025)
The purpose of this counseling is so that children in SDN 1 Sopet grades 1, 2 and 3 can know and can listen together in the classroom about the positive and negative impacts of using gadgets and can know the limits of using these gadgets. The method in this counseling activity has two stages, first, the preparation stage, the facilitator made observations at SDN 1 Sopet. Then conduct deliberations and socialization with the principal, then proceed with determining the target participants. In the implementation stage, the facilitator provides material, guidance and motivation about the influence of gadgets on early childhood, especially children of SDN 1 Sopet grades 1, 2 and 3.